The impact of antimicrobial de-escalation therapy in culture-negative pneumonia: a systematic review and meta-analysis - Jae-Uk Song; Jonghoo Lee (The Korean Journal of Internal Medicine, 2023)
Background/Aims Antimicrobial de-escalation (ADE) remains a challenging strategy in the treatment of pneumonia. We investigated the outcomes of ADE as measured by mortality and duration of the use of antibiotics in patients with culture-negative pneumonia. Methods We performed a systematic review and meta-analysis in accordance with PRISMA guidelines. The primary outcome was inpatient mortality. Results We examined six studies comprising 11,933 subjects, of whom 1,152 received ADE. Overall, the ADE strategy was associated with a statistically lower risk of in-hospital mortality compared with non-ADE (risk ratio [RR] = 0.60, 95% confidence interval [CI] = 0.38 to 0.93). Although substantial heterogeneity was found among the included studies (I2 = 66%), a meta-regression analysis could not reveal plausible sources of heterogeneity. And ADE was associated with a shorter duration of total and initial antibiotic therapies and total length of hospital stay compared with non-ADE. Conclusions Our findings suggest that ADE seems to be significantly associated with better clinical outcomes compared with non-ADE. Caution is demanded when interpreting data of this study because of substantial between-study heterogeneity.